Learning in digital era: Analysis of civic education learning materials for students in junior high school - Devi, Lathifah Sandra; Rejekiningsih, Triana; Rusnaini, Rusnaini (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
This study aims to find out obtain the results of analysis learning materials Civic education in junior high school at digital era. Analysis of civic education learning materials for student in junior high school is focused on Banten Province. This study was conducted using descriptive quantitative approach. The data collection technique used purposive sampling technique. The sample used to obtain the data is junior high school student respondents to civic education in the digitalization era in Banten Province who were randomly selected in Eight grade and consisted of 40 respondents. Data were collected through the process of observation, interviews, and filling out a questionnaire in the form of a questionnaire. The results of this questionnaire data are then processed and made in the form of percentages in the form of tables and figures chart. Analysis of Civic education learning materials for students' junior high school at digital era found that in the learning process, learning materials that use technology are needed so that learning is more creative and innovative. This can be seen based on the percentage of statements agreeing to the needs of students' learning materials civic education in junior high school at digital era, namely 65.4% agree and 34.6% disagree. Then the results of the analysis of the needs of students' teaching materials will be used to design the development of civic education in junior high school teaching materials in the digital era.